Investment Game Application (IGA): A new interactive tablet application for digital product profiling for rice breeding - CGIAR Research Program on Rice (2019)
IGA has been pre-tested in the Philippines and piloted and implemented through large-scale behavioral experiments in eastern India (Odisha and West Bengal), Bangladesh, the Philippines and Cambodia. An R&D License Agreement (021216) has been signed between IRRI and BRRI on 5 December 2016. BRRI is currently using IGA in Bangladesh.